Strengthening Students’ Academic Writing Skills Through the Mendeley Reference Management Application (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
The ability to write scientific papers is an important competency for students; however, they often face challenges in properly managing citations and references. This situation results in poor quality of academic writing and an increased risk of plagiarism due to the continued use of manual reference management methods and limited utilization of technology. This community service activity is intended to enhance students’ knowledge and skills in managing citations and references by strengthening their proficiency in using the Mendeley reference management application. The target participants are students of the English Literature Program, Faculty of Cultural Sciences, Halu Oleo University. The implementation methods included material presentation, application usage demonstrations, and hands-on practice guidance. The results of the activity showed an increase in students’ understanding of citations and their ability to apply Mendeley in academic writing, with an average score increase from 54 on the pre-test to 88 on the post-test, thereby contributing to improved academic writing quality and the prevention of plagiarism.
Keywords: Citation; Mendeley; Scientific Paper